Isolation of Pathogenic Bacteria Causing Clinical Mastitis and Their Susceptibility to Commercial Antibiotics in Dairy Cows - Hassan Ishag Hassan Haren; Eka Handayanta; Ihsan Hilmi; Muhammad Evan Magistrama (Faculty of Animal Husbandry, Wijayakusuma Purwokerto University, 2026)
Clinical mastitis in dairy cattle poses severe economic and health challenges globally, exacerbated by rising antimicrobial resistance (AMR). This systematic review and meta-analysis evaluated the prevalence of mastitis-causing pathogens and their antibiotic resistance profiles from 2010 to 2023. Following PRISMA guidelines, 45 eligible studies were analyzed using a random-effects model. The pooled estimates revealed that Gram-positive bacteria are the primary causative agents, predominantly Staphylococcus intermedius (42.30%) and Staphylococcus aureus (32.97%). Analysis of resistance proportions demonstrated alarming rates against commonly used commercial antibiotics, notably Penicillin (45.2%) and Ampicillin (40.5%). Crucially, methicillin-resistant S. intermedius strains exhibited absolute resistance (100%) to oxacillin and cefoxitin. High inter-study heterogeneity (I² > 75%) was observed, with meta-regression confirming a statistically significant temporal increase in resistance over the past decade. These findings underscore the critical threat of AMR in the dairy sector. The study concludes that there is an urgent necessity for implementing standardized diagnostic procedures, continuous molecular surveillance, and rigorous, evidence-based localized antibiotic stewardship policies to mitigate the spread of resistant pathogens and ensure sustainable dairy production.